The Iron Gamelan Grants Mechanism By The Cultural Department On Mutio Raras Karawitan Art Society 2022 - Haikal, Muhammad Abdurrahman; Agustina, Arinta; Putra, Trisna Pradita (Institut Seni Indonesia Yogyakarta, 2024)
The socio-cultural diversity of Yogyakarta society has the opportunity to foster traditional arts. However, the obstacle felt by the community is the lack of support for cultural facilities and infrastructure. So, the Regional Government needs to intervene to support its development, one of which is in the form of art equipment assistance. In 2022, the Yogyakarta Special Region Cultural Office provided gamelan grants to art groups. The Mutio Raras Karawitan Art Society became one of the recipients of Gamelan grants. Behind the gamelan grant activities carried out, there is a selection mechanism so that the implementation of this grant achieves its goal of preserving traditional artistic values and providing facilities and infrastructure assistance. This research aims to find out, explain, and analyze the mechanism for distributing gamelan grants to the Mutio Raras Karawitan Art Society. This research applies descriptive qualitative methods through data collection techniques from observation, interviews, documentation, and literature studies. The theoretical approach used is distribution management, grants, and gamelan. The results showed that the iron gamelan grant mechanism given to the Mutio Raras Karawitan Art Society in fiscal year 2022 was well implemented. The conclusion of this study is that the mechanism carried out is in accordance with the management theory used, namely, organizing, implementing, and controlling and evaluating. There are obstacles in the implementation stage carried out, namely the lack of human resources, which hinders the efficiency of the work carried out.